The Influence of ChatGPT Usage and Entrepreneurship Education on Students' Entrepreneurial Intentions with Innovative Behaviour as a Mediating Variable : The Perspective of Social Cognitive and Experiential Learning Theory - Sutrisno, Sutrisno; Siminto, Siminto; Syamsuri, Syamsuri; Junianto, Pilifus; Pramono, Susatyo Adhi (LPPM Universitas Pendidikan Mandalika, 2024)
This study aims to examine a model that integrates social cognitive theory and experiential learning theory in the context of using ChatGPT and entrepreneurship education to enhance students' entrepreneurial intention, considering the mediating role of innovative behaviour. This research uses a quantitative approach with a survey method using SEM-PLS data analysis to explore the relationship between the relevant variable. Purposive sampling technique is used to select samples that meet specific criteria. The research sample consisted of 139 students in Yogyakarta, Indonesia, with data collected via an online questionnaire. The study results indicate that the use of ChatGPT, entrepreneurship education, and innovative behaviour positively and significantly influence students' entrepreneurial intentions, in line with social cognitive and experiential learning theory. Innovative behaviour also plays a significant role as a mediating variable. This research suggests that educational institutions can further optimize the use of technology, such as ChatGPT, in entrepreneurship curricula and provide more practical experiences to strengthen students' entrepreneurial intentions.